The correlation between pH and flow rate of salivary smokers related to nicotine levels labelled on cigarettes - Dewi Saputri; Abdillah Imron Nasution; Mutiara Rizki Wardarni Surbakti; Basri A. Gani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: Saliva is a biological fluid in oral cavity that plays a role in maintaining the environmental balance and oral commensal. Nicotine of cigarettes has been reported as a predisposing factor for changing of pH and salivary flow rate, thereby changing in biological salivary components. Purpose: This study aimed to analyze the correlation between salivary pH and salivary flow rate in smokers with nicotine levels labeled on cigarettes. Methods: Purposive sampling was conducted involving 40 male smokers. Before participating, they filled a questionnaire related to the history of their smoking habit. Using a spitting method for 5 minutes their saliva was collected. Results: Result of Pearson correlation test showed that there was a significant correlation between smoking intensity and salivary flow rate of those smokers (r = -0.486 and p<0.001). The results also indicated that there was a significant correlation between smoking intensity and salivary pH (r = -0.376 and p<0.017). On the other hand, there was no significant correlation between nicotine levels levels labeled on cigarettes with salivary pH of those smokers (r = -0.107, p>0.512). There was no correlation between nicotine levels labeled on cigarettes and salivary pH of those smokers (r = -0.216, p>0.181). Nevertheless, there was a significant correlation between salivary flow rate and salivary pH of those smokers (r= 0.686, p<0.00,). Conclusion: There is a strong correlation between the intensity of smoking with salivary flow rate and its pH. However, there is no correlation between nicotine levels labeled on cigarettes and both salivary flow rate as well as salivary pH.